A Legal and Jurisprudential Investigation into Family Rights Antagonism - سید ابوالقاسم حسینی زیدی; خیرالله قیاسی سونکی (آموزه‌‌های فقه مدني)
If there is a dispute among family members due to the antagonism of their rights, it is necessary to prefer the right of one over the other according to the criteria existing in the principles of jurisprudence and law. Some of the most important cases of antagonism in family law are: antagonism of right to housing and headship of family, antagonism of right to divorce and remarriage, antagonism of mother remarriage with custody of child, antagonism between father’s guardianship with child privacy, antagonism of father and mother right in child birth etc. The present research uses a descriptive-analytical method to investigate the antagonism of rights in the family, which also tries to express the solutions to resolve these antagonisms while investigating some cases of antagonism. Considering the preferences expressed in the principles of jurisprudence and the spirit of legal article and solutions provided by the legislator to resolve antagonism cases, it seems that the main goal of the legislator in resolving antagonism and legislation is to maintain the foundation of the family